2020
DOI: 10.1016/j.ihj.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of out-of-Hospital Cardiac Arrests, knowledge of cardiovascular disease and risk factors in a regional setting in India: The Warangal Area out-of-hospital Cardiac Arrest Registry (WACAR)

Abstract: Objective Out-of-Hospital Cardiac Arrest (OHCA) is a global public health problem. There is inadequate data on OHCA in India. The Warangal Area out-of-hospital Cardiac Arrest Registry (WACAR) was planned to understand OHCA in a regional setting in India. Methods WACAR is a prospective one-year observational cohort study of OHCA in the Warangal area, Telangana, India. The study included 814 subjects of OHCA of presumed cardiac etiology brought to the Mahatma Gandhi Memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…A multi-center study conducted in Pakistan showed that nearly 90% of OHCA patients are witnessed, yet only 2.3% received bystander CPR [ 25 ]. The high number of OHCA witness in Pakistan could be attributable to joint family system as most of the cases in this study occurred in residences, similar to what was seen in India [ 26 ]. However, nearly 50% of the witnessed cardiac arrest in European countries receive bystander CPR, particularly in public places [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 68%
“…A multi-center study conducted in Pakistan showed that nearly 90% of OHCA patients are witnessed, yet only 2.3% received bystander CPR [ 25 ]. The high number of OHCA witness in Pakistan could be attributable to joint family system as most of the cases in this study occurred in residences, similar to what was seen in India [ 26 ]. However, nearly 50% of the witnessed cardiac arrest in European countries receive bystander CPR, particularly in public places [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 68%
“…Currently, few studies and international registries provide preliminary data on OHCA in India. 6 , 7 , 13 , 14 , 15 , 16 , 17 , 18 These studies highlight a staggering rate of bystander CPR ranging from 0% to under 10% in these studies, except for a single study reporting bystander CPR delivery up to 27.8%. (WACAR Study) [ Table 1 ].…”
Section: Current Evidence and Review Of Literaturementioning
confidence: 88%
“…The In low-and middle-income countries (LMICs), there is a dearth of literature on OHCA, but poor outcomes are widely reported. 18,19 In Nepal, where the health care system is fragile, and the emergency response system is in its infant stage, it is important to equip first responders with basic life-saving skills. As they are typically the first to respond to rural emergencies, police officers' knowledge of CPR can be beneficial to those in rural settings where, otherwise, no other health care help is available promptly.…”
Section: Discussionmentioning
confidence: 99%